At the edge of the forest : essays on Cambodia, history, and narrative in honor of David Chandler - Hansen, Anne Ruth; Ledgerwood, Judy, 1959-; Chandler, David P. (David Porter), 1933- (Studies on Southeast Asia, 2008)
Inspired by David Chandler's groundbreaking work on Cambodian attempts to find order in the aftermath of turmoil, these essays explore Cambodian history using a rich variety of sources that cast light on Khmer perceptions of violence, wildness, and order, examining the "forest" and cultured space, and the fraught "edge" where they meet.